As raízes discursivas da intervenção militar na Amazônia - SOARES, Filipe Menezes (Universidade Federal do Pará, 2020)
This article aims to compare the attempts of the military dictatorship in the Amazon and the discourses of the early stages of colonization in the region. It is understood that a fundamental part of the archaeological method is the construction of the image archive with certain knowledge relates. Thus, the military rationality that has the Amazonian issue at its core will be investigated in the light of the discourses presented during the first contacts of Europeans with the region. Emphasis will be given to the records of the first conquerors, as well as those who went to the Amazon in the eighteenth century, the so-called naturalistic travelers. Having some of these historical accounts, some comparisons will be made with what the military dictatorship postulates throughout the 1960s and 1980s. The purpose is to compose the roots of derivation of the discourse established by the military to support their policies; point out their references and accuse the dialogue they establish with other historicities.